PENGARUH KEBIJAKAN PEMERINTAH SELAMA MASA PANDEMI COVID-19 TERHADAP MINAT PENUMPANG DI BANDAR UDARA INTERNASIONAL SUPADIO PONTIANAK - Haryadi, Dedi Dwi; Awan, Awan (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The existence of several government policies that have been mentioned above have an impact on some operational activities at Supadio International Airport becoming unstable. One of them is a decrease in passengers. This research is included in the quantitative research category because quantitative data is used to estimate the effect of Covid-19 on passenger interest at Supadio Pontiank Airport, and how much influence Covid-19 has on passenger interest at Pontianak Supadio Airport. Data collection techniques using Observation, Questionnaire and Documentation. This research method uses multiple linear regression using the T test, F test with a significance level of 5%. Based on the results of the research conducted, it was concluded that there was a significant influence of government policies on passenger interest at Pontianak Supadio Airport. The magnitude of the influence seen from the large R Square shows the large influence of the variable (X) of government policy on the variable (Y) which is 0.373 = 37.3%. This means that the magnitude of the influence of the government policy variable on passenger interest is 37.3% while the rest is in other factors. The regression equation also shows the magnitude of Y = 24.127 + 0.785X. The coefficient b is called the coefficient of regression direction and represents the average change in the Y variable for each X variable.